Uganda : Technical Assistance Report-Initiating the Stock-Taking of the Public Investment Program. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the initiation of the stock-taking of the public investment program in Uganda. This stock-taking will provide a basis for better budgeting by providing information on the existing multi-year project commitments, and the incremental recurrent costs for operation and maintenance of the assets delivered. It will also identify a basic information structure for each project and subsequently collect a data baseline, providing a foundation for more robust project monitoring. It will aid the management of the overall project portfolio. By identifying the scale of existing multi-annual commitments, it will avoid adding projects to the investment pipeline, which cannot be financed under the Medium Term Expenditure Framework.